Attack of the Fougeray Castle (engraving) - Auteur inconnu (Wikimedia Commons, 1883)
Notice iconographique issue de Wikimedia Commons. Titre: Attack of the Fougeray Castle (engraving). Attack of the Fougeray Castle in 1354 (engraving)
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; Patrimoine; Wikimedia Commons; Iconographie